Perspectives on the teaching of academic writing for performing arts students - Javier Caballero, Gabriela Luisa (2020)
Starting academic life represents a problem to new comers into higher education. This situation is aggravated in the case of students in art-related majors, as there is a pre-conception that these disciplines are oriented towards the development of artistic skills only. However, university life also implies the development of other skills related to academic life. Considering these difficulties, we present in this text some perspectives about the teaching of essay writing and research at university level. We propose that the content of the student’s major field of studies courses should be articulated with the research practice by means of writings that evidence the textualization of the artistic practice, knowledge that is valuable in the specialization.